Céline Sciamma Portraits - Wilson, Emma (Edinburgh University Press, 2021)
Céline Sciamma is the most visible and important feminist, and lesbian, director in contemporary international filmmaking. Her fourth feature, Portrait of a Lady on Fire, competed for the Palme d'Or at Cannes in 2019, and intervened directly in debates about the female gaze, sexuality, and specifically how to look at and make a portrait of young women. In her approach to female, non-binary and queer identities, she has focused on the need for agency, binding this imperative into her aesthetic choices and modes of filmmaking. This is the first book-length study of Sciamma's films, focusing on the relationship of her work to the visual arts, and exploring the relevance of feminist theory to her unique perspective.